Bromide: the good, the bad, and the ugly of the oldest antiseizure medication - Gouveia, Diogo; Mandigers, Paul; Cherubini, Giunio Bruto (Frontiers in Veterinary Science, 2024)
Bromide is the first effective antiseizure medication used in human medicine since the XIX century. Initially met with skepticism, bromide quickly gained enthusiasm within the medical field until being largely replaced by newer antiseizure medications with significantly fewer adverse effects in people. In veterinary medicine, bromide continues to be used in the management of epileptic patients for over 30 years, yet adverse effects can impact owners and patients alike. We sought to provide the general practitioner and veterinary neurologist with insightful information on both the positive and negative attributes of bromide, explore factors that may influence its desirability as an antiseizure medication in specific veterinary cases and elucidate its current role in modern epilepsy treatment for veterinary patients. It’s also our endeavor to discuss the current use as an alternative or add-on with other known antiseizure medications and potential future studies that might enhance our understanding and use of this medication.